2009
DOI: 10.1177/193229680900300616
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Organ Transplantation

Abstract: A discussion of hyperglycemia during organ transplantation is a broad topic that includes patients with a known history of diabetes pretransplant, those at risk for post-transplant diabetes, those with stress-induced hyperglycemia, those with hyperglycemia related to immunosuppressive therapy, and hyperglycemia in the deceased organ donor. In contrast to the plethora of articles and studies describing perioperative and critical care management of hyperglycemia in cardiac, trauma, and medical/surgical intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Bars with different superscript letters are significantly differentiation from each other (*Po 0.05). aggravating inflammatory response and ischemic organ damage (Hekmat and Eshraghi, 2010;Marvin and Morton, 2009). Acute and chronic HG were reported to be associated with increased apoptosis, mitigated activities targeted to organ protective pathways, impaired nitric oxide (NO) availability (Giugliano et al, 1997), and excessive reactive oxygen species production during I/R (Capes et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Bars with different superscript letters are significantly differentiation from each other (*Po 0.05). aggravating inflammatory response and ischemic organ damage (Hekmat and Eshraghi, 2010;Marvin and Morton, 2009). Acute and chronic HG were reported to be associated with increased apoptosis, mitigated activities targeted to organ protective pathways, impaired nitric oxide (NO) availability (Giugliano et al, 1997), and excessive reactive oxygen species production during I/R (Capes et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Additional investigations of hyperglycemia prevention and management are needed. 10 We hope that our study will provide some knowledge in this area.…”
Section: Ender Gedik Et Al/experimental and Clinical Transplantation mentioning
confidence: 86%
“…The vast majority of studies are abstracts of congress and retrospective studies performed in large centers. 9,10 The management of hyperglycemia during the perioperative period is always a challenge to anesthesiologists, surgeons, and intensivists. Over the years and throughout the literature, controversy has surrounded the blood glucose target levels and methods for controlling it.…”
Section: Living-donor Liver Transplant (Ldlt) Is An Important Treatmementioning
confidence: 99%
“…[104][105][106][107] There are insufficient data regarding peritransplant glycemic control, although it has been suggested that graft function may be affected by plasma glucose levels. [108][109][110][111][112][113] Perioperative hypoglycemia is of great concern because of the predisposition to its development in patients with liver dysfunction and altered glycogen stores, and especially those with ALF. Continuous infusion is typically initiated in the OR to maintain glycemic control and continued postoperatively.…”
Section: Renal Considerationsmentioning
confidence: 99%